Estudio de factibilidad para la creación de una caja de ahorros y crédito en la parroquia "La Libertad", cantón Espejo, provincia del Carchi. - Chacón Morales, Carlos Andrés (2013)
In our country, the population of La Libertad The parish located in the canton Mirror, Carchi is with other groups of small and medium producers, indigenous, peasants, Afroecuatorians and popular urban residents, a sector given its condition is unfortunately excluded or have limited access to financing rather classic offered by traditional financial intermediaries such as banks and credit unions.